1997
DOI: 10.1002/(sici)1097-0339(199701)16:1<47::aid-dc11>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Fine-needle aspiration of pigmented villonodular synovitis of the temporomandibular joint masquerading as a primary parotid gland lesion

Abstract: The fine‐needle aspiration findings in a case of pigmented villonodular synovitis of the temporomandibular joint are presented. The characteristic cytomorphologic and clinical features of this uncommon, benign fibrohistiocytic lesion are discussed. In addition, due to the initial clinical impression of a primary parotid gland lesion, the differential diagnosis for the cytomorphologic features observed (histiocytoid cells admixed with osteoclast‐like giant cells) are discussed within the context of a primary sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…Many salivary gland lesions can be accurately diagnosed by FNA cytology. [3456] The aspiration smears of TGCT are usually characteristic and show variable numbers of multinucleated giant cells dispersed in the background of the mononuclear histiocytoid cells. [178] The histopathologic differential diagnosis of giant cell-rich lesions in the salivary glands is extensive [Table 1].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many salivary gland lesions can be accurately diagnosed by FNA cytology. [3456] The aspiration smears of TGCT are usually characteristic and show variable numbers of multinucleated giant cells dispersed in the background of the mononuclear histiocytoid cells. [178] The histopathologic differential diagnosis of giant cell-rich lesions in the salivary glands is extensive [Table 1].…”
Section: Discussionmentioning
confidence: 99%
“…[1] It is very rare for these tumors to be encountered in the parotid gland, and the differential diagnosis can be considerably challenging, especially when involvement of the adjacent joint is inconspicuous. Although histologic features of this entity have been adequately reported in the literature,[23] only a few reports have described the cytology of TGCT involving the parotid gland. [3]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PVNS is often misdiagnosed because of the low incidence and atypical symptoms. Of the reported cases, approximately 20% were diagnosed as parotid tumours before operation, and several cases was thought to be TMJ disorders 1,4,9,19,22 . Advanced imaging methods, including computed tomography (CT) and MRI help to determine the correct diag-…”
Section: Discussionmentioning
confidence: 99%
“…Intracranial extension has also been reported in some severe case 2,7,8,11,21 . It is often misdiagnosed as parotid tumour or disorder of the TMJ because of the low incidence and atypical presentations 1,4,9,19,22 Arthroscopy of the TMJ was introduced by Ohnishi in 1975, and is a clinically useful procedure in the diagnosis and treatment of various TMJ diseases. The authors reported a case of simultaneous PVNS and synovial chondromatosis of the TMJ that was successfully treated with arthroscopy in 2009 3 .…”
Section: Pigmented Villonodular Synovitis (Pvns)mentioning
confidence: 99%